A novel weighing cell for KRISS kibble balance - Yoon, Kyung Taek; Lim, Hyun Ho; Kang, Sung Hoon; Kim, Dongmin; Choi, Young Man (European Society for Precision Engineering and Nanotechnology, Conference Proceedings - 19th International Conference and Exhibition, EUSPEN 2019, 2019)
Kibble balance, also known as Watt balance, is an important instrument to measure a newly defined ‘Kg’, which is derived from Planck’s constant. In the KRISS Kibble balance, difference between gravitational force and electromagnetic force is measured by a weighing cell. To lower the uncertainty of measured mass, designing a high precision weighing cell is critical. In this paper, we introduce a novel weighing cell, which is designed especially for the KRISS Kibble balance. To obtain a high repeatability of Kibble balance, the proposed weighing cell is designed based on electromagnetic force compensation (EMFC) that the weight is compensated by electromagnetic force controlled through a feedback algorithm and null position sensor. The weighing cell is also designed symmetrically by using triple compound flexure mechanism, which is radially arranged from the motion axis, to minimize parasitic movements except axial movement. Also, a symmetric tripod lever mechanism is designed for improving measurement sensitivity. Performance of the proposed weighing cell was evaluated through an experiment. Electric compensation range is ±75 g, and repeatability is 1.59 mg measured with E2 class 10 g test mass.
Keywords: Electromagnetic force compensations; Electromagnetic forces; Feedback algorithms; Flexure mechanism; Gravitational forces; Lever mechanism; Measurement sensitivity; Position sensors; Electromagnetic force compensation (EMFC); Kibble balance; Weighing cell